Penyuluhan Kesehatan tentang Pencegahan Penyakit Diare dan Menjaga Kesehatan Lingkungan di Puskesmas Langsa Timur - Intan Bahrina; Etika Sari; Yusriati Yusriati (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
Diarrhea is caused by viral, bacterial or parasitic infections that spread through contaminated food or drink, as well as poor environmental conditions which are the habitat of pathogens. The aim of this activity is to provide education and information to the public about diarrhea so that it is hoped that it can reduce cases of diarrhea and increase public knowledge about the prevention and treatment of diarrhea and its relationship to environmental health. The community service method is carried out by providing counseling and education to the community. The results obtained are that the public understands diarrhea and preventing diarrhea. So that people can take early precautions if diarrhea occurs in family members. Apart from that, people must also maintain health, both the environment and food, in order to avoid disease.